CFTR Gene Mutations and their Role in Male Infertility: A Case Study - Namrata Anjankar; Akash More; Ashish P. Anjankar; Sanket S. Mahajan; Neha Nawale (Journal of Pharmacy and Bioallied Sciences)
The F508del CFTR gene mutation primarily leads to cystic fibrosis development yet produces infertility complications in males. The presented case concerns a 32-year-old man who has azoospermia but does not display cystic fibrosis symptoms. Testing showed the presence of the F508del CFTR mutation, which resulted in identifying obstructive azoospermia with congenital absence of the vas deferens (CAVD). The woman suffered from inadequate ovarian function. Fertility solutions for couples can be obtained through assisted reproductive methods which include testicular sperm extraction (TESE) along with percutaneous epididymal sperm aspiration (PESA) that utilizes intracytoplasmic sperm injection techniques (ICSI). Genetic counseling remains essential for risk assessment because it tells family members if they carry this genetic defect. The assessment matters more when women also have the genetic defect. The research confirms how CFTR mutations affect infertility while demonstrating the need for early genetic screening to properly manage male infertility with unknown causes.